PENGARUH STOCK SPLIT DAN VOLUME PERDAGANGAN TERHADAP LIKUIDITAS SAHAM PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2012 - 2015 - Zunita Fiantimala; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTSince 1996, capital market development in Indonesia have a tremendousdrowth . In this research the writer will discuss about stock split factor andtrading volume which can influence stock liquidity. The purpose of this study are:(1) To know and analyze whether stock split and trading volume simultaneouslyaffect on stock liquidity at companies that go public in c. (2) To know and analyzewhether stock split and trading volume have partial effect to liquidity of share atcompany which go public in Indonesia Stock Exchange. (3) To know and analyzewhich among the stock split and trading volume that dominantly influence theliquidity of shares in companies that go public in Indonesia Stock Exchange.This research uses the type of research that is replication of development,when viewed from its type, this research includes Explanatory Reseach. Thisresearch takes samples from the population using Purposive Sampling techniqueor Judgment Sampling method. The result of this research is simultaneously, stocksplit and trading volume have significant effect to stock liquidity. Partially, stocksplit variable has significant effect on stock liquidity and trading volume has noeffect on stock liquidity. While the dominant variable affecting stock liquidity isstock split.Keywords : Stock Split, trading volume, stock liquidity.